Bio-desalination of sea water using floating plants; A laboratory experiment on three mangroves species - Hidayani, Mesalina Tri; Wulandari, Sri; Heriansah, Heriansah; Agusma, Elmi Novrianti (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
The plant species mangrove has been knowed to be effective for the bio-desalination process. However, there is currently no scientific evidence supporting the ability of mangrove bio-desalination when implemented through the floating method. This laboratory-scale study aimed to evaluate the bio-desalination of several mangrove species using the floating method. This study consisted of four treatments and three replicates. Treatments included a control group without mangroves (treatment A) and three treatments using mangroves (treatments B, C, and D), Bruguiera sp., Rhizophora sp., and Avicennia sp., which were positioned floating in a tank using a tray. During the eight weeks of rearing, nutrients were provided through 60 mL liquid NPK fertilization. The results showed that there was a decrease in salinity concentration in all mangrove treatments between 22.5-23.9 ppt from the initial salinity of 30 ppt. Different results were observed for the treatment without mangroves, and the salinity concentration tended to increase until the end of the research to 31.6 ppt. The highest Salinity Reduction Efficiency (SRE) was achieved by Avicennia sp.. (25.1%), followed by Rhizophora sp. (22.8%), and the lowest in Bruguiera sp. (20.3%). The results of this study showed that bio-desalination using mangroves had a significant effect on SRE, and each treatment indicated a significant difference (p<0.05). The results of this study provide initial evidence of the potential of the mangrove floating method for bio-desalination of seawater into brackish water.